Risk factors for child death during an intimate partner homicide: a case-control study - Lyons, Vivian H. (Child maltreatment, 2021)
Corollary victims represent approximately 20% of all intimate partner homicides (IPH), and many are children. We used National Violent Death Reporting System (NVDRS) data (2003?2017) to compare all IPH incidents with a child corollary victim (n = 227) to all IPH incidents where a child was present but not killed (n = 350). We examined risk factors for child fatality during an IPH. For each risk factor, we calculated the odds ratio for child death during the IPH, adjusting for multiple comparisons. Perpetrator history of suicidal behavior, rape of the intimate partner victim, a non-biological child of the perpetrator living in the home, and perpetrator job stressors increased odds while prior separation of the IPV victim from the perpetrator decreased the odds of a child death during an IPH incident. To our knowledge, this is the first case-control study using live-controls within NVDRS and can help direct prevention efforts for child death during IPH.